Labor Supply Decisions, Occupational Segregation, and Intergenerational Income Mobility – Germany and the United States Compared - Eberharter, Veronika (Journal of Income Distribution®, 2009)
The article directs attention to the structuring effects of humancapitalvariables and family-background characteristics on labor supplydecisions, occupational segregation, and intergenerational incomemobility in the United States and Germany - two countries with differentinstitutional labor market settings and family role patterns. Thearticle tests the hypothesis that the impact of family-background characteristicson labor supply decisions, sex or gender segregation, andintergenerational transmission of social and economic status is moreexpressed in societies with traditional role patterns. Using data fromthe international version of the Cross-National Equivalent File (PSIDGSOEP),the results of the static labor supply model show that genderand education significantly determine the individual labor market participationin both the countries. Occupational gender segregation ismore pronounced in Germany than in the United States. The contributionof the occupational groups to total gender segregation differsby country but not by marital status. We find stronger evidence forthe impact of individual- and family-background characteristics on theintergenerational heritage of social status in the United States than inGermany.